Traffic Management and Engineering Based on Traffic Modeling in the Gilingan Area, Banjarsari, Surakarta City - Lutfi Mohammad Hakim (Green Publisher Indonesia, 2025)
This study examines the traffic performance in the Gilingan area, Banjarsari District, Surakarta City, which has experienced rapid growth following the construction of the Masjid Raya Syeikh Zayed and the planned Islamic Center. The existing condition reveals daily congestion, particularly along Ahmad Yani and S. Parman roads, due to road narrowing and limited crossing infrastructure. To address these issues, the study employed field surveys and secondary data analysis, including traffic volume measurements, V/C Ratio calculations based on the Indonesian Road Capacity Guidelines (PKJI) 2023, and microsimulation using VISSIM. Three traffic management and engineering intervention scenarios were tested: (1) optimizing APILL, installing medians, and constructing sidewalks; (2) enforcing parking regulations and optimizing integrated parking facilities with public transport; and (3) implementing a one-way system through a Giratory System. Results indicate that Scenario 3 provides the most significant improvement, with the V/C Ratio reduced from 0.51 to 0.49, an increase in average road speed, a reduction in intersection delay from 23.59 seconds per vehicle to 13.98 seconds per vehicle, and a substantial decrease in congestion cost. These findings affirm that the one-way system is the optimal solution for enhancing traffic service in the Gilingan area, offering valuable insights for transportation policy-making.